Analysis of Supply Chain Management Practices on Private Banks in Indonesia - Armen, Armen; Putu Wiagustini, Ni Luh; Rahyuda, Henny; Gede Sri Artini, Luh (International Journal of Supply Chain Management, 2020)
Abstract— This study examines the role of profitability in mediating the effects of supply chain on market structure, GDP growth, inflation rates and exchange rates. This research was conducted at Bank Indonesia of all banking companies namely the National Non-Foreign Exchange Private Bank in Indonesia. Based on a purposive sampling technique, the number of samples (n) from data time series every year during the 2013-2017 period is 15 company samples, so the total sample of research for 5 years is 75 observations. The analysis used in this study is Path analysis or path analysis. Based on the analysis, overall credit risk at Non-Foreign Exchange Commercial Banks during the 2013-2017 period was influenced by internal factors (capital and liquidity ratios) and external factors (GDP growth) with Profitability as Moderating that occurred between the ratio of capital, liquidity and GDP growth to risk credit. Supply chain strategy has a significant positive effect on profitability at Non-Foreign Exchange Commercial Banks during the 2013-2017 period. Bank size has a significant positive effect on profitability in Non-Foreign Exchange Commercial Banks during the 2013-2017 period. Liquidity has a significant positive effect on profitability at Non-Foreign Exchange Commercial Banks during the 2013-2017 period. GDP growth has a significant positive effect on profitability at non-foreign exchange commercial banks during the 2013-2017 period. Inflation has no significant positive effect with profitability at Non-Foreign Exchange Commercial Banks during the 2013-2017 period. The exchange rate (exchange rate) has a significant positive effect on profitability at non-foreign exchange commercial banks during the 2013-2017 period. Supply chain strategy has a significant positive effect on credit risk at Non-Foreign Exchange Commercial Banks during the 2013-2017 period. GDP growth has a significant positive effect on credit risk at non-foreign exchange commercial banks during the 2013-2017 period. Inflation has no significant positive effect on credit risk at Non-Foreign Exchange Commercial Banks during the 2013-2017 period. The exchange rate (Exchange) has no significant positive effect on credit risk at Non-Foreign Exchange Commercial Banks during the 2013-2017 period. Profitability does not have a significant positive effect on credit risk at Non-Foreign Exchange Commercial Banks during the 2013-2017 period. Profitability only mediates the relationship between the ratio of capital, liquidity and GDP growth to credit risk. The management must establish metrics in supply chain and show a clear link on all performance indicators.